Experimental and Numerical Study of Stagnant Zones in Pebble Bed - Xinlong Jia; Xingtuan Yang; Nan Gui; Yu Li; Jiyuan Tu; Shengyao Jiang (Science and Technology of Nuclear Installations)
The experimental method (side area method) and DEM simulation have been carried out to analyse the stagnant zone in the quasi-two-dimensional silos. The side area method is a phenomenological method by means of investigating the interface features of different areas composed of different coloured pebbles. Two methods have been discussed to define the stagnant zone. In particular, the area of the stagnant zone has been calculated with the mean-streamline method, and the tracking time of different marking pebbles has been investigated with the stagnant time method to explore the kinematics characteristics of the pebbles. The stagnant zone is crucial for the safety of the pebble-bed reactor, and the practical reactor core must avoid the existence of the stagnant zone. Furthermore, this paper also analyses the effects of bed configuration (the bed height, the base angle, and the friction coefficient) on stagnant zone with the two methods mentioned above. In detail, the bed height shows little impact on the stagnant zones when the bed height exceeds a certain limit, while the base angle has negative prominent correlation with the stagnant zone. The friction coefficient effect seems complicated and presents the great nonlinearity, which deserves to be deeply investigated.